2018
DOI: 10.1093/femsyr/foy064
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic defects in fission yeast lipid metabolism ‘cut’ mutants are suppressed by ammonium chloride

Abstract: Fission yeast ‘cut’ mutants show defects in temporal coordination of nuclear division with cytokinesis, resulting in aberrant mitosis and lethality. Among other causes, the ‘cut’ phenotype can be triggered by genetic or chemical perturbation of lipid metabolism, supposedly resulting in shortage of membrane phospholipids and insufficient nuclear envelope expansion during anaphase. Interestingly, penetrance of the ‘cut’ phenotype in mutants of the transcription factor cbf11 and acetyl-coenzyme A carboxylase cut6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…However, it remains an open question whether ammonium chloride rescues cut by directly affecting PL synthesis or whether it acts more indirectly by affecting processes unrelated to lipid metabolism but connected to mitotic progression. Interestingly, we found that the presence of ammonium chloride increases lipid droplet content in wild type S. pombe cells (Zach et al, ), which indicates that it can indeed affect lipid metabolism. Notably, the ned1 S627A/S629A mutant, which is unable to upregulate PL biosynthesis during mitosis, is not viable and cells are cut even in the presence of abundant ammonium chloride (Makarova et al, ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, it remains an open question whether ammonium chloride rescues cut by directly affecting PL synthesis or whether it acts more indirectly by affecting processes unrelated to lipid metabolism but connected to mitotic progression. Interestingly, we found that the presence of ammonium chloride increases lipid droplet content in wild type S. pombe cells (Zach et al, ), which indicates that it can indeed affect lipid metabolism. Notably, the ned1 S627A/S629A mutant, which is unable to upregulate PL biosynthesis during mitosis, is not viable and cells are cut even in the presence of abundant ammonium chloride (Makarova et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…Whereas in the complex yeast extract with supplements (YES) medium the incidence of cut mitoses is high in cut6–621 and cbf11∆ mutants, the mitotic defects are largely suppressed when mutant cells are grown in the Edinburgh minimal medium (EMM) defined medium, or upon genetic disruption of nutrient‐sensitive signaling pathways of protein kinase A (Pka1) and stress‐activated protein kinase (Sty1/Spc1; Převorovský et al, ; Převorovský et al, ). We have recently shown that the crucial suppressive component of EMM is ammonium chloride, a good nitrogen source, suggesting that nitrogen source availability and/or nitrogen‐dependent signaling play an important role in the successful progression through mitosis in S. pombe (Zach et al, ). However, it remains an open question whether ammonium chloride rescues cut by directly affecting PL synthesis or whether it acts more indirectly by affecting processes unrelated to lipid metabolism but connected to mitotic progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “cut” phenotype has been in this case ascribed to insufficient FA production and membrane PL supply during anaphase, when rapid expansion of the nuclear envelope takes place. Recently, it was observed that the cut6 mutant phenotype, together with the “cut” phenotype caused by the deletion of the transcription factor cbf11 , can be suppressed by supplementation of the growth medium with ammonium chloride (Zach et al, ). Cbf11 is a transcription factor which regulates the expression of several genes involved in lipid metabolism, including cut6 (Prevorovsky et al, ; Prevorovsky et al, ).…”
Section: Phospholipid Precursorsmentioning
confidence: 99%
“…Reaksi yang terjadi, yaitu : NH3 +HCl NH4Cl ΔH= -175,7 kJ/mol Reaksi berlansung secara eksotermik, dan panas yang dibangkitkan yang digunakan untuk menguapkan sebagian besar air, ada ketika asam klorida (33)(34)(35)(36)(37) cair digunakan. Ammonium klorida (23,26,27,29) dapat dihasilkan lewat kristalisasi.…”
Section: Proses Netralisasi Lansungunclassified